AMERICAN BEAUTY STANDARD IMPACT ON THE MAIN CHARACTER OF ISN'T IT ROMANTIC MOVIE - Ridha Ikhva Erviana; Linda Meylinda; Umi Hani (LPPM Universitas PGRI Jombang, 2026)
This study aims to analyse the representation of American beauty standards in the film Isn’t It Romantic (2019) and examine their impact on the main character’s personal, social, and psychological experiences. The object of this research is the film directed by Todd Strauss-Schulson, which is uniquely positioned as a romantic comedy that simultaneously critiques and reinforces conventional beauty ideals within American popular culture. This research employed a qualitative descriptive method, with data analysis presented in writing through interpretative and critical examinations of scenes, dialogues, and character interactions. Naomi Wolf’s concept of the beauty myth served as the primary theoretical framework for analysing how beauty standards function as a form of social control across various aspects of life, including gender relations, media representation, and workplace dynamics. The findings reveal that American beauty standards are prominently constructed and normalised in both societal and professional environments, particularly through media portrayal, social expectations, and institutional practices. Furthermore, the study identifies four major impacts of these beauty standards on the main character: psychological pressure, lowered self-esteem, appearance-based inequality, and a gradual process of self-acceptance.